Teachers’ lifelong learning competencies - Kazu, İ Yaşar; Erten, Pınar (Ankara University, 2016)
Lifelong learning, which reveals as a result of globalization and being information society, aims to provide that individuals are the ones who learn to learn throughout their lives by basing upon learning from the cradle to the grave. In accordance with this purpose, the roles and competencies of educational institutions and especially teachers that are effective in the lifelong learning come into prominence. It was tried to be determined the competencies of teachers according to their ages, branches, genders, experiences and faculties with this study. The universe of this research which was prepared according to descriptive survey model is formed with the teachers who work at the primary schools, secondary schools and high schools in Kahramanmaraş in 2013-2014 academic year. The sample is consisted of 295 teachers who are chosen randomly from these schools. The data were collected by being applied the scale of ‘Lifelong Learning Competencies’ to the teachers. It was determined that the teachers have a high competency in the LLP and its sub-dimensions in the consequence of this research. The opinions of the teachers, which are about LLP and its sub-dimensions, were evaluated according to the ages, genders, branches, experiences and faculties of the teachers. In accordance with these results, it is emphasized that the implementations related to lifelong learning should be backed up and be increased and should become integrated with information and communication technology. © 2016, Ankara University. All rights reserved.
Öğretmenlerin yaşam boyu öğrenme yeterlikleri
Keywords: Competencies of acquiring information; Competencies of decision-taking; Competencies of initiative and entrepreneurship; Competencies of learning how to learn; Digital competencies; Lifelong learning; Self-management competencies